1992
DOI: 10.2307/1130909
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and Cognition in High-Functioning Children with Autism

Abstract: This study compares the ability of nonretarded autistic children (9-16 years of age) with the ability of normally developing children (9-14 years of age) to discriminate between various emotional states, to take the perspective of another regarding emotional states, and to respond affectively. The children's understanding of conservation was also assessed. While the children with autism did surprisingly well on the empathy-related measures, they performed less well than the normal children on these measures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(67 citation statements)
references
References 0 publications
6
59
0
2
Order By: Relevance
“…Although individuals on the autistic spectrum may not show deficits in basic emotion recognition (Loveland et al, 1997; Grossman et al, 2000), they do have deficits in recognizing complex emotions (Yirmiya et al, 1992; Baron-Cohen et al, 2001). The use of a graded developmental scale of emotion comprehension may help reveal such deficits in clinical populations, should they exist, and enable researchers to quantify the degree of developmental delay in emotion lexicon comprehension relative to typical age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although individuals on the autistic spectrum may not show deficits in basic emotion recognition (Loveland et al, 1997; Grossman et al, 2000), they do have deficits in recognizing complex emotions (Yirmiya et al, 1992; Baron-Cohen et al, 2001). The use of a graded developmental scale of emotion comprehension may help reveal such deficits in clinical populations, should they exist, and enable researchers to quantify the degree of developmental delay in emotion lexicon comprehension relative to typical age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Thus social-emotional difficulties in ASD may not arise because of a lack of motivation per se but because of a lack of understanding what emotional signals afford. Support for this argument stems from the studies by Sigman and Kasari and colleagues outlined earlier in which autistic children were consistently less responsive to the emotional displays of others (Loveland and Tunali, 1991; Sigman et al, 1992; Yirmiya et al, 1992) despite demonstrating an awareness of the emotional displays in question (Bacon et al, 1998; Corona et al, 1998). The behavioral self regulation view is also in line with studies that demonstrate typical physiological but atypical behavioral separation anxiety in autistic children (Willemsen-Swinkels et al, 2000; Sigman et al, 2003) and more generally it helps to explain why studies of emotion perception tend to yield less consistent behavioral differences between ASD and non-ASD groups than studies examining the ability to use such expressions to regulate interpersonal exchanges.…”
Section: The Social-emotional Difficulties Associated With Asdmentioning
confidence: 96%
“…For instance, it is fairly consistently reported that autistic individuals are less likely than non-autistic individuals to direct emotional expressions at others during naturalistic interactions (Snow et al, 1987; Macdonald et al, 1989; Mundy and Sigman, 1989; Yirmiya et al, 1989; Dawson et al, 1990; Kasari et al, 1990, 1993; Sigman et al, 1992; Dissanayake et al, 1996; Charman et al, 1997; Joseph and Tager-Flusberg, 1997; Bieberich and Morgan, 1998; Zwaigenbaum et al, 2005; Hobson et al, 2009; Hudenko et al, 2009). Autistic individuals also tend to mimic the facial expressions of others less frequently and consistently than non-autistic individuals (McIntosh et al, 2006; Beall et al, 2008; Stel et al, 2008; Oberman et al, 2009; but, see Magnée et al, 2007; see also Sims et al, 2012) and they share the emotional experiences of others in a qualitatively different manner than comparison groups (Yirmiya et al, 1992; Baron-Cohen and Wheelwright, 2004; Lombardo et al, 2007; Rogers et al, 2007; Dziobek et al, 2008; Hobson et al, 2009; Hurdy and Slaughter, 2009; Minio-Paluello et al, 2009a; Bird et al, 2010; Greimel et al, 2010; Schulte-Rüther et al, 2011; Schwenck et al, 2011; see also the discussion between Minio-Paluello et al, 2009b; Smith, 2009). Although findings in this context are not always consistent (see Begeer et al, 2008), the weight of the evidence overall leaves little doubt that ASD is characterized by anomalies in multiple facets of interpersonal affective behaviors, and the real life consequences of these have been documented in a series of elegant naturalistic observations by Sigman and Kasari and their colleagues (Sigman et al, 1992; Dissanayake et al, 1996; Corona et al, 1998; see also Loveland and Tunali, 1991; Bacon et al, 1998; see also Hobson et al, 2009).…”
Section: The Social-emotional Difficulties Associated With Asdmentioning
confidence: 99%
“…Research focused on emotional dysfunctions and theoretical accounts have emphasized the notion that the mechanisms mediating the self-regulation of behavior during social–emotional exchanges are severely impaired in ASDs (Yirmiya et al, 1992; Hobson, 1993). Pioneer studies reported that difficulties in children with ASDs might arise with both basic emotions (fear, disgust, anger) and social cognitive emotions (pride, embarrassment, shame) that are related to introspection and self-reflection (Capps et al, 1995; Loveland et al, 1997; Kasari et al, 2001; Heerey et al, 2003).…”
Section: The Relevance Detector Theory Of Autismmentioning
confidence: 99%